2021
DOI: 10.3389/fpubh.2021.705777
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Privacy Protection With the Growth of AI-Empowered Online Shopping Based on the Evolutionary Game Model

Abstract: Social distancing due to the COVID-19 pandemic has driven some consumers to online shopping, and concerns about pandemic risks and personal hygiene have increased the demand for e-commerce. Providing personalized recommendations seems quite profitable for e-commerce platforms, and consumers also benefit from personalized content with the advancement of AI technologies. However, this possible win-win situation is marred by the increase in consumers' privacy concerns. Technical solutions have been widely studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…In this regard, being “ omni ” has obtained much attention as a new business model aimed at integrating all available channels within a firm and eliminating the barriers among these channels ( 47 ). Specifically, omnichannel is defined as “ a unified approach that manages channels as intermingled touch points to allow consumers to have a seamless experience within an ecosystem ” ( 4 , 10 , 11 , 28 , 29 , 46 ). In the omnichannel context, consumers are not limited by the channels' characteristics and can migrate across them without any information loss or reiteration.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, being “ omni ” has obtained much attention as a new business model aimed at integrating all available channels within a firm and eliminating the barriers among these channels ( 47 ). Specifically, omnichannel is defined as “ a unified approach that manages channels as intermingled touch points to allow consumers to have a seamless experience within an ecosystem ” ( 4 , 10 , 11 , 28 , 29 , 46 ). In the omnichannel context, consumers are not limited by the channels' characteristics and can migrate across them without any information loss or reiteration.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Consistent with much PMT-related literature that excluded response costs from the research framework [e.g., see ( 33 , 72 )], responses costs were excluded in our conceptual framework. This approach was taken since numerous studies have suggested that omnichannel retailing is a novel technology that forms a seamless retail world for consumers, and the adoption of such shopping methods does not require additional efforts and does not cause advantage losses to other shopping methods ( 11 , 29 , 73 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, COVID-19 remains one of the most serious threats to public health despite the recent development and distribution of COVID-19 vaccines (6)(7)(8). From May 24 to May 30, 2021, the number of new COVID-19 cases and deaths continued to decrease, with over 3.5 million new cases and 78,000 new deaths reported globally.…”
Section: Introductionmentioning
confidence: 99%